Motivation of luxury consumption among Generation Y and senior consumers in China - LAW, WING YAN (2015)
Abstract Generation Y has become the new powerhouse in the Chinese luxury market since the last decade. Despite the global economic crisis in 2009, the growth rate of luxury market in China remains impressive. Chinese consumers, especially the Generation Y, have become the major contributor of such dynamic growth in luxury market. Without doubt, increasing consumers are engaging in the purchase of luxury products; however, little is known about the motivation behind their consumptions. This dissertation attempts to investigate the motivations of Generation Y and senior consumer toward luxury consumptions, in regarding to their changing attitudes, perceptions and intentions that affected by internal and external factors, in order to discover the reasons behind the purchase. Aggressive GDP growth in China has transferred into high purchase power and thus lead the country irrefutably become the most attractive market for global luxury brands. Culture factors such as individualism and collectivism are influential for consumers’ motivations from different aspects. Specifically, this study is designed to examine the effects of those drivers toward luxury purchase intentions. This study has conducted semi-structure interviews with 8 Generation Y and 5 seniors to identify and corroborate the motivating factors behind their luxury consumptions. The motivation between Generation Y and senior consumers are differ in the extent of their culture, values, and other factors, which will be addressed in this study.